Factors Affecting Consumers’ Decision in Purchasing MUI Halal-Certified Food Products - Qurroh Ayuniyyah; Didin Hafidhuddin; Hambari Hambari (Institute for Research and Community Empowerment (LPPM TAZKIA), 2016)
As the largest Muslim population in the world, Indonesia has a promising potential of halal food industry in terms of economic and market values. This research aims at analyzing factors affecting consumers’ decision in purchasing MUI halal-certified food products by employing survey method and descriptive analysis approach. Three hundred respondents are selected using non-probability convenience sampling technique and are analyzed using multiple regression. The criteria of the respondents are Muslim and have bought Indonesian halal-certified food products in the last one-month. While the dependent variable in this study is purchasing decision (Y), the four independent variables are cultural and religious factors (X1), social factor (X2), personal factor (X3) and psychological factor (X4). This study finds that the four independent factors significantly influence consumers’ decision in purchasing MUI halal-certified food products. However, social factor are negatively related with the consumers’ purchasing decision. This study is expected to deliver the information on the halal food purchasing decisions from the perspective of the customers in order to provide recommendations to develop halal food industry in Indonesia.